Convergence of Traditional and Online Property Crime Victimization in a City with Little Offline Crime - Milani, Riccardo (Victims & offenders, 2022)
This paper analyzes the correlates of traditional (burglary, vehicle theft, theft from vehicles, and pickpocketing) and online property crime (data theft and online fraud), with particular attention given to the relation between them and the risk of multiple victimizations. Data are gathered from a large and representative victimization survey conducted in a Swiss city (N = 7,885). The findings suggest that both traditional and online property victimization are related positively to the participants’ lifestyle routines, physical and online protection measures, and educational level. Men, young persons, those employed actively, and university graduates are overrepresented among the multiple victims of online-offline property victimization.